Small vessel disease pathological changes in neurodegenerative and vascular dementias concomitant with autonomic dysfunction. (16th August 2019) - Hase, Yoshiki; Polvikoski, Tuomo M.; Firbank, Michael J.; Craggs, Lucinda J. L.; Hawthorne, Emily; Platten, Charlotte; Stevenson, William; Deramecourt, Vincent; Ballard, Clive; Kenny, Rose Anne; Perry, Robert H.; Ince, Paul; et al.
Abstract: We performed a clinicopathological study to assess the burden of small vessel disease (SVD) type of pathological changes in elderly demented subjects, who had clinical evidence of autonomic dysfunction, either carotid sinus hypersensitivity or orthostatic hypotension or both or had exhibited unexpected repeated falls. Clinical and neuropathological diagnoses in 112 demented subjects comprised dementia with Lewy bodies (DLB), Parkinson's disease with dementia (PDD), Alzheimer's disease (AD), Mixed dementia (mostly AD‐DLB) and vascular dementia (VaD). Of these, 12 DLB subjects had no recorded unexpected falls in life and therefore no evidence of concomitant autonomic dysfunction. A further 17 subjects were assessed as aging controls without significant pathology or signs of autonomic dysfunction. We quantified brain vascular pathological changes and determined severities of neurodegenerative lesions including α‐synuclein pathology. We found moderate‐severe vascular changes and high‐vascular pathology scores ( P < 0.01) in all neurodegenerative dementias and as expected in VaD compared to similar age controls. Arteriolosclerosis, perivascular spacing and microinfarcts were frequent in the basal ganglia and frontal white matter (WM) across all dementias, whereas small infarcts (<5 mm) were restricted to VaD. In a sub‐set of demented subjects, we found that vascular pathology scores were correlated with WM hyperintensity volumes determined by MRI in life ( P < 0.02). Sclerotic index values were increased by 50% in both the WM and neocortex in all dementias compared to similar age controls. We found no evidence for increased α‐synuclein deposition in subjects with autonomic dysfunction. Our findings suggest greater SVD pathological changes occur in the elderly diagnosed with neurodegenerative dementias including DLB and who develop autonomic dysfunction. SVD changes may not necessarily manifest in clinically overt symptoms but they likely confound motor or cognitive dysfunction. We propose dysautonomia promotes chronic cerebral hypoperfusion to impact upon aging‐related neurodegenerative disorders and characterize their end‐stage clinical syndromes.